Single nucleotide polymorphisms on Cholecystokinin B Receptor gene as a candidate gene for crowing in Pelung chickens. - Asmara, Indrawati Yudha; Hilmia , Nena; Garnida, Dani (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to explore mutation based on single nucleotide polymorphism (SNP) in the Cholecystokinin B receptor (CCKBR) gene of Pelung chickens. Materials and Methods: We collected DNA samples from 48 Pelung roosters that had won the crowing competition. The CCKBR target encompasses exon 3, intron 3, exon 4, and a part of intron 4, a long 601 bp. This target was replicated using PCR with specific primers that were designed by Primer-BLAST from NCBI. We generated the nucleotide sequence from the PCR product’s sequencing results. The SNP analysis was done by BioEdit and MEGA. Genotyping and haplotyping were done based on nonsynonymous single nucleotide polymorphisms (SNPs) on exons 3 and 4. We calculated allele and genotype frequency, heterozygosity, and Hardy-Weinberg Equilibrium (HWE) using POPGENE 32 programs. Results: This study found three nonsynonymous single nucleotide polymorphisms. The nsSNP in exon 3 altersthe coding for the 210th amino acid from serine to asparagine (g.1290 G > A/S210N), while the SNPs in exon 4 alter the coding for the 232nd amino acid from valine to phenylalanine (g.1423G > T/V232F) and the 243rd amino acid that changes the amino acid valine to glycine (g.1457T > G/V243G). The frequency of the mutated alleles is lower than the unmutated alleles. However, the mutation at position g.1457T > G/V243G produces a higher frequency than the unmutated allele. The allele and genotype frequency were not in HWE. It was caused by intensive selection in Pelung chickens, especially for growing capacity. Conclusion: Nonsynonymous mutation on CCKBR may cause variations in the crowing and other traits such as the growth of Pelung chickens. Further studies are needed to explore the CCKBR gene, including the relationship of the gene with the vigor and/or stress level of Pelung chickens. J. Adv. Vet. Anim. Res., 12(1): 141–148, March 2025 http://doi.org/10.5455/javar.2025.l881